Rapport Balai Citoyen - Zerbo, Armel (Fluid Ontologies of Contestation. Social media, anti-government protest and transnational decolonization movements in Burkina Faso, 2023)
The document offers an analysis of Internet users' comments in connection with the publications made on the Balai Citoyen official page from October 28 to 31, 2014.
Keywords: Social media; Decolonisation; Fluid Ontology; Manifestant; Protester; Right to Resist